Nicolas Laurence, La contestation portée par les innovations monétaires comme moteur de changement institutionnel. Le cas des monnaies locales et des cryptomonnaies - Nicolas Laurence (Revue de la Régulation)
Monetary innovations convey a contestation of the existing monetary system. Local currencies and cryptocurrencies participate in this process. Local currencies convey a monetary contestation focused on social aspects and ecology at the territorial and local level, while cryptocurrencies, whose Bitcoin is the most emblematic initiative, thanks to the blockchain technology, contest the monetary system by offering transnational alternatives. The thesis aims to demonstrate that these two radically different monetary innovations convey alternative political projects which participate in the same process of emergence of new monetary spaces potentially carrying institutional change.The challenge raised by these monetary innovations is first grasped in its discursive dimension before being analysed when it takes the form of collective actions through semi-structured interviews. Resorting to a political economy of money allows us to question the place of power relations and conflicts in the process of monetary institution evolution.